Implementasi Pembelajaran Tari Tradisional dalam Membentuk Karakter Disiplin, Kerja Sama, dan Percaya Diri Peserta Didik di Sanggar Tari Sang Citra Budaya Surakarta - Orlendita, Monica Lintang; Jazuli, Muhammad (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study aims to analyze the implementation of traditional dance learning in developing students’ discipline, cooperation, and self-confidence at Sanggar Tari Sang Citra Budaya Surakarta. This study employed a descriptive qualitative approach with the studio leader, instructors, and students as research subjects. Data were collected through observation, interviews, and documentation. The results show that the implementation of traditional dance learning is carried out through three stages: planning, implementation, and evaluation. The planning stage includes determining learning materials, arranging practice schedules, and grouping students based on their ability levels. The implementation stage emphasized discipline in attendance, active participation in group practice, and readiness for performances. Discipline is reflected in punctuality and compliance with instructors’ directions, cooperation is shown through interaction and coordination among students, while self-confidence develops through performance experiences. In addition, instructors act as facilitators, motivators, and mentors in the learning process, while students show positive responses toward the activities. Evaluation was conducted by observing the development of students’ technical skills and attitudes during the learning process. Thus, traditional dance learning functions as an effective medium for character education. These findings indicate that practice-based traditional dance learning can serve as a character education model in nonformal education through habituation, direct experience, and students’ emotional engagement